2014
DOI: 10.1007/s13277-014-2782-3
|View full text |Cite
|
Sign up to set email alerts
|

Alisertib (MLN8237), a selective Aurora-A kinase inhibitor, induces apoptosis in human tongue squamous cell carcinoma cell both in vitro and in vivo

Abstract: Aurora-A kinases are overexpressed in many cancer tissues and cells. Alisertib is an investigational, orally administered, selective, small-molecule Aurora-A kinase inhibitor with preclinical activity against a broad range of tumors. Our study was aimed to detect the effects of alisertib on human tongue squamous cell carcinoma (HTSCC). Treatment of a human tongue squamous cell carcinoma cell line, HSC-3, with alisertib to inhibition of Aurora-A kinases reduced proliferation and induced apoptosis, which was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Similar to many previous studies on the molecular mechanisms of action of MLN8237 (11, 19, 22, 5356), we demonstrated that apoptosis and cell cycle arrest in G 2 /M phase mediated the antitumor activity in pGBM both in vitro and in vivo . Despite the significantly prolonged animal survival time in IC-4687GBM, all the animals in the treatment group died of disease.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to many previous studies on the molecular mechanisms of action of MLN8237 (11, 19, 22, 5356), we demonstrated that apoptosis and cell cycle arrest in G 2 /M phase mediated the antitumor activity in pGBM both in vitro and in vivo . Despite the significantly prolonged animal survival time in IC-4687GBM, all the animals in the treatment group died of disease.…”
Section: Discussionsupporting
confidence: 90%
“…In preclinical data, Alisertib has been able to achieve robust anti-tumour efficacy that rationalized its further advancement to clinical trials (36)(37)(38)(39)(40)(41). Growth inhibition was achieved in a wide range of cell cultures, including cells originating from HTLV-1 infected adult T-cell leukemia (42), peripheral T-cell lymphomas (37), multiple myeloma (38), human tongue squamous cell carcinoma (39), malignant bladder cancer (40), and cervical cancer (36) cell lines. The latter were able to be completely cured in mouse xenograft models (36).…”
Section: Introductionmentioning
confidence: 99%
“…97-101 A number of xenografted-mouse studies have shown remarkable growth inhibition of solid tumours or haematologic malignancies when treated with alisertib alone or in combination with other anticancer agents. 22,[102][103][104][105][106]…”
Section: Mechanism Of Action and Binding Mode Of Alisertibmentioning
confidence: 99%